Performance analysis of DC/DC bidirectional converter with sliding mode and pi controller - Chandra Shekher Purohit; Geetha M.; Padmanaban Sanjeevikumar; Pandav Kiran Maroti; Shruti Swami; Vigna K. Ramachandaramurthy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
A sliding mode controller for a non-isolated DC/DC, bidirectional converter is presented and comparative study with PI controller is done along with ISE analysis, in order to do performance analysis. The proposed system can be utilized in many applications such as electrical vehicle, distributed power generation or small grids. Second theorem of Lyapunov is utilized and stability of the closed loop system is mathematically proven. The adopted control strategy achieves effective output voltage regulation and good dynamic stability. Rejection of disturbance is also an inherent characteristic of this technique. Furthermore, it is illustrated that the system can successfully follow changes of load demand and compensates sudden disturbances in operating condition. The design is evaluated and verified using Matlab/Simulink. Results of Matlab simulation are provided to show the feasibility of the proposed system and effectiveness of control method. Simulation results show that this technique can provide a considerable edge over control techniques which are presently available (applied) over this type of converter.